Inheriting Tradition: Acculturation at the Naek Ayun Ceremony of Kutai Community in Kutai Kartanegara Regency - Sukapti Sukapti; Aljasiyah Elsa Suhandita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Naek Ayun ceremony which is thought to be a legacy of pre-Islamic traditions is still practiced by the Kutai people in Kutai Kartanegara Regency, who are generally Muslim.The continuity of the pre-Islamic tradition to date is the result of negotiations and acculturation between pre-existing cultures and Islam.This study was conducted to see the forms of cultural crossing or acculturation that occurred and the meaning of the ceremony for the participants in the present. The field research was conducted in Tenggarong District, Kutai Kartanegara Regency, using a qualitativedescriptive method.Based on the results of this study, it can be predicted that the existence of the Naek Ayun ceremony which has its roots in pre-Islamic times willcontinue in the future.The procession and meaning of the Naek Ayun ceremony are inherited by the new generation dynamically through the stages of being processed, created, and renewed with the tasmiyah ceremony.The general meaning behind the series of activities and symbols of the Naek Ayun ceremony is an expression of gratitude to God for the grace that has been bestowed uponthe society.In addition, the Naek Ayun ceremony means maintaining good relations between humans and their environment.